Cyclin D3 Is Selectively Required for Proliferative Expansion of Germinal Center B Cells - Matthew H. Cato; Suresh Chintalapati; Irene W. Yau; Sidne A. Omori; Robert C. Rickert (2010)
The generation of robust T-cell-dependent humoral immune responses requires the formation and expansion of germinal center structures within the follicular regions of the secondary lymphoid tissues. B-cell proliferation in the germinal center drives ongoing antigen-dependent selection and the generation of high-affinity class-switched plasma and memory B cells. However, the mechanisms regulating B-cell proliferation within this microenvironment are largely unknown. Here, we report that cyclin D3 is uniquely required for germinal center progression. Ccnd3(-/-) mice exhibit a B-cell-intrinsic defect in germinal center maturation and fail to generate an affinity-matured IgG response. We determined that the defect resulted from failed proliferative expansion of GL7(+) IgD(-) PNA(+) B cells. Mechanistically, sustained expression of cyclin D3 was found to be regulated at the level of protein stability and controlled by glycogen synthase kinase 3 in a cyclic AMP-protein kinase A-dependent manner. The specific defect in proliferative expansion of GL7(+) IgD(-) PNA(+) B cells in Ccnd3(-/-) mice defines an underappreciated step in germinal center progression and solidifies a role for cyclin D3 in the immune response, and as a potential therapeutic target for germinal center-derived B-cell malignancies.